Trichothecene biosynthesis in Fusarium species: chemistry, genetics, and significance. - Desjardins, A E (1993)
Several species of the genus Fusarium and related fungi produce trichothecenes which are sesquiterpenoid epoxides that act as potent inhibitors of eukaryotic protein synthesis. Interest in the trichothecenes is due primarily to their widespread contamination of agricultural commodities and their adverse effects on human and animal health. In this review, we describe the trichothecene biosynthetic pathway in Fusarium species and discuss genetic evidence that several trichothecene biosynthetic genes are organized in a gene cluster. Trichothecenes are highly toxic to a wide range of eukaryotes, but their specific function, if any, in the survival of the fungi that produce them is not obvious. Trichothecene gene disruption experiments indicate that production of trichothecenes can enhance the severity of disease caused by Fusarium species on some plant hosts. Understanding the regulation and function of trichothecene biosynthesis may aid in development of new strategies for controlling their production in food and feed products.